(untitled) (Research, Society and Development, 2023)
Care with the structure of accounting courses has been gaining attention in recent years and the change in the practices of fundamental disciplines in the aggregation of knowledge, experience and service to the community is relevant, since the insertion of components that add to the development of the student help in maintaining a good professional. Among these components, a nucleus of forensic accounting practices stands out, which does not yet exist at the Federal University of Maranhão, Imperatriz campus. This work objective was to investigate the knowledge and behavior of students at this educational institution and to verify the judgment of a proposed intention to implement a core of forensic accounting practices. 59 students answered a questionnaire in virtual environments and the answers obtained were analyzed qualitatively and quantitatively. Most survey participants know the real importance of good teaching of accounting expertise and its well-performed practice. Most of the students only qualified “accounting expertise” and its technologies, requiring improvements in the efficiency of learning and in the theoretical-practical relationship to have skillful knowledge to work in this area that is of interest to the sample, having as its main ally the core of practices of accounting expertise that already exists in other institutions. In the end, the participants converge on the need to implement this core of practices at the Federal do Maranhão in Imperatriz, requiring the development of an implementation and inspection project so that a future core can start activities serving society.